Adaptive management of natural resources—framework and issues - Williams, Byron K. (Journal of Environmental Management, 2011)
Adaptive management, an approach for simultaneously managing and learning about natural resources, has been around for several decades. Interest in adaptive decision making has grown steadily over that time, and by now many in natural resources conservation claim that adaptive management is the approach they use in meeting their resource management responsibilities. Yet there remains considerable ambiguity about what adaptive management actually is, and how it is to be implemented by practitioners. The objective of this paper is to present a framework and conditions for adaptive decision making, and discuss some important challenges in its application. Adaptive management is described as a two-phase process of deliberative and iterative phases, which are implemented sequentially over the timeframe of an application. Key elements, processes, and issues in adaptive decision making are highlighted in terms of this framework. Special emphasis is given to the question of geographic scale, the difﬁculties presented by non-stationarity, and organizational challenges in implementing adaptive management.

Improving our legacy: Incorporation of adaptive management into state wildlife action plans - Fontaine, Joseph J. (Journal of Environmental Management, 2011)
The loss of biodiversity is a mounting concern, but despite numerous attempts there are few large scale conservation efforts that have proven successful in reversing current declines. Given the challenge of biodiversity conservation, there is a need to develop strategic conservation plans that address species declines even with the inherent uncertainty in managing multiple species in complex environments. In 2002, the State Wildlife Grant program was initiated to fulﬁll this need, and while not explicitly outlined by Congress follows the fundamental premise of adaptive management, ‘Learning by doing’. When action is necessary, but basic biological information and an understanding of appropriate management strategies are lacking, adaptive management enables managers to be proactive in spite of uncertainty. However, regardless of the strengths of adaptive management, the development of an effective adaptive management framework is challenging. In a review of 53 State Wildlife Action Plans, I found a keen awareness by planners that adaptive management was an effective method for addressing biodiversity conservation, but the development and incorporation of explicit adaptive management approaches within each plan remained elusive. Only w25% of the plans included a framework for how adaptive management would be implemented at the project level within their state. There was, however, considerable support across plans for further development and implementation of adaptive management. By furthering the incorporation of adaptive management principles in conservation plans and explicitly outlining the decision making process, states will be poised to meet the pending challenges to biodiversity conservation.

An Introduction to Adaptive Management for Threatened and Endangered Species - Runge, Michael C. (Journal of Fish and Wildlife Management, 2011)
Management of threatened and endangered species would seem to be a perfect context for adaptive management. Many of the decisions are recurrent and plagued by uncertainty, exactly the conditions that warrant an adaptive approach. But although the potential of adaptive management in these settings has been extolled, there are limited applications in practice. The impediments to practical implementation are manifold and include semantic confusion, institutional inertia, misperceptions about the suitability and utility, and a lack of guiding examples. In this special section of the Journal of Fish and Wildlife Management, we hope to reinvigorate the appropriate application of adaptive management for threatened and endangered species by framing such management in a decision-analytical context, clarifying misperceptions, classifying the types of decisions that might be amenable to an adaptive approach, and providing three fully developed case studies. In this overview paper, I define terms, review the past application of adaptive management, challenge perceived hurdles, and set the stage for the case studies which follow.

Learning to ADAPT: monitoring and evaluation approaches in climate change adaptation and disaster risk reduction – challenges, gaps and ways forward - Silva Villanueva, Paula (IDS, 2011)
This working paper is a methodological contribution to the emerging debate on monitoring and evaluation (M&E) in the context of climate change adaptationand disaster risk reduction. Effectively managing disaster risk is critical for adapting to the impacts of climate change, however disasters risk reduction M&E practice may be limited in capturing progress towards adaptation. The unique nature of adaptation to climate change calls for experience-based learning M&E processes for discovering the key insights into adaptive capacity and its links to adaptation processes, and to risk and vulnerability reduction at large. The ADAPT guiding principles and indicators set the foundations towards this end.

Making Good Use of Adaptive Management - Doremus, Holly; Andreen, William L.; Camacho, Alejandro E.; Farber, Daniel A.; Glicksman, Robert L.; Goble, Dale D.; Karkkainen, Bradley C.; Rohlf, Dan; Tarlock, A. Dan; Zellmer, Sandra B.; Jones, Shana Campbell; Huang, Yee (Center for Progressive Reform, 2011)

Essentials of Utilization-Focused Evaluation - Patton, Michael Quinn (SAGE Publications, 2011)
Based on Michael Quinn Patton's best-selling Utilization-Focused Evaluation, this briefer book provides an overall framework and essential checklist steps for designing and conducting evaluations that actually get used. The new material and innovative graphics present the utilization-focused evaluation process as a complex adaptive system, incorporating current understandings about systems thinking and complexity concepts. The book integrates theory and practice, is based on both research and professional experience, and offers new case examples and cartoons with Patton's signature humor.
Google-Books-ID: BaMgAQAAQBAJ
Keywords: Reference / Research; Research

Salt River Ecosystem Restoration Project - Adaptive Management Plan - Harvey, H.T. (Humboldt County Resource Conservation District, 2011)

A guide to monitoring and evaluating policy influence - Jones, Harry (ODI, 2011)

Taking responsibility for complexity: how implementation can achieve results in the face of complex problems - Jones, Harry (ODI, 2011)
OCLC: 837825712

Strategies for learning from failure - Edmondson, Amy C. (Harvard Business Review, 2011)

Design thinking: understand - improve - apply - Plattner, Hasso; Meinel, Christoph; Leifer, Larry (Springer, 2011)
"In this book, the researchers take a system's view that begins with a demand for deep, evidence-based understanding of design thinking phenomena. They continue with an exploration of tools which can help improve the adaptive expertise needed for design thinking. The final part of the book concerns design thinking in information technology and its relevance for business process modeling and agile software development, i.e. real world creation and deployment of products, services, and enterprise systems"–Cover
Keywords: Creative ability in business; Creative thinking; Designer; Industrial management; Innovation; Organizational change; Product development; System design; Technological innovations

Putting vulnerability to climate change on the map: a review of approaches, benefits, and risks - Preston, Benjamin L.; Yuen, Emma J.; Westaway, Richard M. (Sustainability Science; Dordrecht, 2011)
There is growing demand among stakeholders across public and private institutions for spatially-explicit information regarding vulnerability to climate change at the local scale. However, the challenges associated with mapping the geography of climate change vulnerability are non-trivial, both conceptually and technically, suggesting the need for more critical evaluation of this practice. Here, we review climate change vulnerability mapping in the context of four key questions that are fundamental to assessment design. First, what are the goals of the assessment? A review of published assessments yields a range of objective statements that emphasize problem orientation or decision-making about adaptation actions. Second, how is the assessment of vulnerability framed? Assessments vary with respect to what values are assessed (vulnerability of what) and the underlying determinants of vulnerability that are considered (vulnerability to what). The selected frame ultimately influences perceptions of the primary driving forces of vulnerability as well as preferences regarding management alternatives. Third, what are the technical methods by which an assessment is conducted? The integration of vulnerability determinants into a common map remains an emergent and subjective practice associated with a number of methodological challenges. Fourth, who participates in the assessment and how will it be used to facilitate change? Assessments are often conducted under the auspices of benefiting stakeholders, yet many lack direct engagement with stakeholders. Each of these questions is reviewed in turn by drawing on an illustrative set of 45 vulnerability mapping studies appearing in the literature. A number of pathways for placing vulnerability mapping on a more robust footing are also identified. [PUBLICATION ABSTRACT]
Keywords: Climate change; Mapping; Risk assessment; Sustainable development